Adam Chełmoński (1890–1959) i jego udział w pracach Zespołu Prawa Cywilnego Materialnego Komisji Kodyfikacyjnej PRL - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
The book concerns the figure of one of the most outstanding Polish lawyers in the first years after the Second World War – professor Adam Chełmoński (1890-1959). His achievements went back to the interwar period (including research and teaching work at the Stefan Batory University in Vilnius, advocate activity, work in the Codification Committee of the Second Polish Republic). However, the scientist achieved the highest position in the Polish legal community working at the University of Wrocław and, above all, working within the Substantive Civil Law Team of the Codification Commission of the Polish People’s Republic. The appointment to this Team was a recognition of the professor’s knowledge and scientific achievements. In the aforementioned body, A. Chełmoński collaborated with the greatest Polish civilians of the post-war period, some of whom had also codification experience gained from the Codification Commission of the Second Polish Republic (J. Wasilkowski, K. Przybyłowski). This book presents the figure of professor Chełmoński with the separation of various types of his activities in the pre-war and post-war period, and the work of this scientist in the Substantive Civil Law Team of the Codification Commission. From the point of view of post-war changes, Chełmoński has been burdened with a baggage of experiences from the Second Polish Republic, which was very negative for the communist authorities (interwar period law professor at the University of Vilnius, educated in Tsarist Russia, member of one of the governments of the Second Polish Republic, co-creator of pre-war, “bourgeois” law within the Codification Commission of the Second Polish Republic), and after the Second World War Chełmoński was a non-party person. The scientist – wanting to find himself in the new political and social reality – writes several scientific papers that fitted into the assumptions of Marxist science. His post-war scientific interests obviously had to fit the needs of the socialist legal system. Otherwise, the scientist would not have a chance to be employed at the Faculty of Law of a state university. On the other hand, in these new and difficult conditions for the freedom of science, Chełmoński did not lose sight of the older issues, such as the freedom of contracts, legal and trading security, or the legal personality of companies. As a member of the Codification Commission of the Polish People’s Republic, the scientist missed several meetings, but when he was present, he actively tried to participate in the work of the Substantive Civil Law Team. He proved to be an active debater who spoke on many issues on the agenda of the Team. Moreover, his activity was expressed in submitting motions or amendments to the proposed solutions, and even in formulating conclusions leading to the reassumption of previously adopted resolutions. A large part of his proposals was appreciated by the Team members. Not surprisingly, the scientist was most active when he acted as a co-authorof the regulations in question – this applies to selected provisions of the general part of obligations (i.e. general provisions on contractual obligations, performance of obligations and the consequences of non-performance obligations) and several named contracts contained in the special part of the book of obligations (i.e. agency contract, commission contract, storage contract, shipping contract, contract of carriage, bank account). Looking at the process of creating the Polish Civil Code, the death of A. Chełmoński took place after the Team adopted the draft code in the first reading. Therefore prof. Chełmoński worked only in the first phase of the development of the Polish Civil Code, but his work should be assessed as very valuable and constructive.
Keywords: Chełmoński, Adam (1890-1959); historia prawa polskiego; prawnicy polscy; Komisja Kodyfikacyjna II Rzeczypospolitej Polskiej; prawo cywilne; Zespół Prawa Cywilnego Materialnego